2012
DOI: 10.5539/jfr.v1n1p200
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Micrococcaceae and Staphylococcaceae throughout the Manufacture of Dry-Cured Lacón (a Spanish Traditional Meat Product) Made without or with Additives

Abstract: Micrococcaceae and Staphylococcaceae were enumerated (on SPC agar + 7.5% NaCl) in samples from the surface and the interior of pieces of dry-cured lacón (a Spanish traditional meat product), at different stages of the manufacturing process, and from six different batches (three made without and three with additives -glucose, sodium nitrite, sodium nitrate, sodium ascorbate, and sodium citrate-). The use of additives did not affect the counts or evolution of this microbial group.For four batches (two without an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 42 publications
(59 reference statements)
0
3
0
Order By: Relevance
“…In the present study, the pH value was found to be over 5.5 in all pastırma samples. Similarly, the absence of true lactic fermentation has been observed in other cured meat products such as French dry-cured hams (16) and dry-cured lacon (17,18). Contrary to pH, water activity is an important hurdle effect in pastırma.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…In the present study, the pH value was found to be over 5.5 in all pastırma samples. Similarly, the absence of true lactic fermentation has been observed in other cured meat products such as French dry-cured hams (16) and dry-cured lacon (17,18). Contrary to pH, water activity is an important hurdle effect in pastırma.…”
Section: Discussionmentioning
confidence: 79%
“…equorum was identified in all pastırma groups. This species was also found in other meat products that were processed as whole pieces (5,6,18,(34)(35)(36). However, this species can be confused with S. xylosus when phenotypic and biochemical methods are used for identification (6,27).…”
Section: Discussionmentioning
confidence: 94%
“…Further, S. epidermidis is increasingly being recognized as reservoir of genes required for natural adaptation on its host tissues that are in turn acquired by other predominantly pathogenic species, like S. aureus 7 8 9 . Apart from human, S. epidermidis is a remarkably diverse species reported in a multitude of diverse environments such as fermented sausage 10 11 , dry-cured lacon 12 13 , domesticated animals 14 as well as from wild mouse species 15 and meat 16 .…”
mentioning
confidence: 99%